O potencial da experimentação no desenvolvimento de habilidades cognitivas e na construção de conhecimento(s) de física no ensino fundamental - Moro, Leandro Silva (2013)
This work shows that many researches are being carried out in Brazil and abroad about the process of teaching and learning in physics, based on different constructivist approaches. Accordingly, the purpose of this work was to use simple experiments in a problematic and investigative way in order to stimulate the development of certain cognitive abilities, as well as the construction of knowledge in physics. We have used the Meaningful Learning Theory of David Ausubel as theoretical reference. The research was conducted with fifteen students in the 9th grade of elementary school, divided into two groups, belonging to a public school in the city of Uberlândia, Minas Gerais. Regarding the field of research, there was an educational experience that has been developed over four classes, which were prepared according to the Three Pedagogical Moments of Delizoicov, Angotti and Pernambuco. Data collection took place in three stages: first, it was applied some problematizations to all students, with the title of Previous Activity; later, the experiments were conducted (Float or Sink? Will the bag hold out?) and finally, the Final Activity, containing questions related to the contents worked, but different. The results indicate that activities permitted incite the students and possibly raise their level of cognitive process, because they required the students the capability to establish relationships between what they knew in the Physics and what was presented to them. Thus, it is considered that experimentation contributes effectively in the development of cognitive skills, since it provides a more active student, allowing that the student to be challenged and experience some important conditions for the teaching-learning process: simultaneous manipulation of objects and ideas; invention; discover by the senses and logical reasoning, a greater involvement of learners in the classroom, which enhances the possibility of test their knowledge, it creates a good climate for teaching and learning, since students are somehow seduced, to realize that he can control some variables when it comes to physical phenomena.